The role of semantic interference in limiting memory for the details of visual scenes - Melcher, David; Murphy, Brian (Frontiers in Psychology, 2011)
Many studies suggest a large capacity memory for briefly presented pictures of whole scenes. At the same time, visual working memory of scene elements is limited to only a few items. We examined the role of retroactive interference in limiting memory for visual details. Participants viewed a scene for five seconds and then, after a short delay containing either a blank screen or ten distracter scenes, answered questions about the location, color and identity of objects in the scene. We found that the influence of the distracters depended on whether they were from a similar semantic domain, such as “kitchen” or “airport”. Increasing the number of similar scenes reduced, and eventually eliminated, memory for scene details. Although scene memory was firmly established over the initial study period, this memory was fragile and susceptible to interference. This may help to explain the discrepancy in the literature between studies showing limited visual working memory and those showing a large capacity memory for scenes.